ANALISIS CAPITAL ADEQUACY RATIO (CAR), NON PERFORMING LOAN (NPL), LOAN TO DEPOSIT RATIO (LDR) DAN SUKU BUNGA SERTIFIKAT BANK INDONESIA (SBI) TERHADAP KEBIJAKAN PENYALURAN KREDIT PERBANKAN - Atria Mariana Devi, 09.05.52.0096 (Students Journal of Accounting and Banking, 2013)
The objective of this research is to analyze the effect of some variables to the banking credit ditribution. It is therefore necessary to test of the analysis Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), Loan to Deposit Ratio (LDR) and the interest rate of Bank Indonesia Certificate (SBI). This research on banking on BEI as one research object, upon the research period from year 2007-2011.The analysis technique used is multiple linear regression and classical assumption among normality test,multicollinearity test, autocorrelation test and heteroscedasticity test. Hypothesis testing using the F test and t test.Testing that has been done in this study proves that Capital Adequacy Ratio (CAR) and Non Performing Loan (NPL) influences negative and significant toward the banking credit distribution. Loan to Deposit Ratio (LDR) influences positive and significant toward the banking credit distribution. Meanwhile the interest rate of Bank Indonesia Certificate (SBI) influences negative and not significant toward the banking credit distribution.Keywords: the banking credit distribution, Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), Loan to Deposit Ratio (LDR) and the interest rate of Bank Indonesia Certificate (SBI)